ANALISIS KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN KONSUMEN DENGAN MENGGUNAKAN METODE SERVPERF-IPA-CSI - Annisa Azzahra Handriati; Sunaryo Sunaryo; Vembri Noor Helia (Faculty of Industrial Technology Universitas Islam Indonesia, 2015)
Customer satisfaction is the most important aspect in order to improve services of Jombor bus station in Sleman-Yogyakarta. The research aims to find out service performance provided in the Jombor bus station, and to give an overview of vicinity condition which can be used to improve services quality for the customer. Methods used in this research are: Service performance (Servperf), Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI). Servperf method with five measuring attribute such as tangibles, responsiveness, assurance, empathy, reability is used to determine the rate of service performance. Furthermore, there are 17 questions provided in order to collect the data. Based on Importance Performance Analysis, there are four service attributes having high level of interest, and low service performance. They are: fineness, cleanliness, and mildness of passenger waiting room, and praying room, also the bus condition, and the safety of bus station zone. The result shows that consumers feel less satisfied with services provided by Jombor bus station management. It because based on the calculation of customer satisfaction index, value 71% is classified as poor condition. Several advices have been given in order to improve the consumer satisfaction such as, inspection of bus condition, renovation of passenger waiting room, rest room, and praying room including the availability of electric equipment such as: speaker, microphone, CCTV, and announcement board. Moreover, in order to reduce the air pollution, the Jombor bus station is suggested to grow some plants in its environment.